Human papillomavirus and other risk factors in Lithuanian cervical carcinoma patients - GUDLEVIČIENĖ, Živilė; SMILGEVIČIŪTĖ-IVSHIN, Alė; VAITKUVIENĖ, Aurelija; ŠEPETIENĖ, Agnė; DIDŽIAPETRIENĖ, Janina (Acta medica Lituanica, 2010)
Background. Cervical cancer is the second biggest cause of female cancer mortality worldwide and the most common cancer in women in Lithuania. The incidence of cervical cancer is strongly associated with HPV prevalence. However, not only HPV infection plays a crucial role in cervical cancer development; other risk factors which vary in different populations and geographical regions as well as HPV prevalence are important. The aim of this study was to detect the HPV, its type’s prevalence and other cervical cancer risk factors for Lithuanian women. Materials and methods. 191 women with primary diagnosed invasive cervical cancer (cases group) and 397 control women were invited to participate in the study. All women were interviewed and samples for HPV testing were taken. Results. In the cases group, 92.7% of women and in the control group 26.7% were infected by HPV (p < 0.0001). HPV 16 was the most common type in both groups. HPV infection increases the risk of cervical cancer 75 times (OR = 75.39; 95% CI 33.61–192.98). Women with lower education, workers, those who started sexual intercourses before 20 years of age, at older age of the first menstrual period, 3–5 or more childbirths, smokers and with a long ago or never performed Pap test are at a significantly higher risk of cervical cancer development. Other non-HPV risk factors were not associated with cervical cancer risk. Conclusions. Data of our study show a high prevalence of HPV in Lithuanian population. It may have an impact on the biggest cervical cancer incidence. The other risk factors are similar as in other lower economic resource countries. Keywords: HPV, cervical cancer, risk factors